Inflammation as a mediator between neck adipose tissue and tumor aggressiveness in hypopharyngeal and laryngeal squamous cell carcinoma - Yu Jiang; Xiaodong Ji; Shanshan Gao; Xiaohuang Yang; Qing Li; Zhuo Yu; Xilong Yang; Zhuo Shen; Jie Shen; Shuang Xia (Cancer Imaging)
Abstract Background The impact of neck adipose tissue (NAT) on the invasiveness of hypopharyngeal squamous cell carcinoma (HPSCC) and laryngeal squamous cell carcinoma (LSCC) remains uncertain. We investigated the roles of NAT and derived - neutrophil to lymphocyte ratio (dNLR) in the aggressiveness of HPSCC and LSCC, and established an adipose- inflammation-aggressiveness axis to identify high-risk factors. Methods This retrospective study involved 412 patients with HPSCC or LSCC. Clinical characteristics, body mass index (BMI), NAT and dNLR were collected and calculated. Logistic regression models, restricted cubic splines (RCS) and mediation analysis were employed to evaluate the associations between NAT, dNLR and the aggressiveness of HPSCC and LSCC. Results The cohort included 412 patients (mean age, 63 years; 93.69% male). Lower NAT was independently associated with advanced TNM stage (adjusted Odds Ratio [OR], 0.54; p = 0.015) and tumor local invasion (adjusted OR, 0.53; p = 0.008). Higher dNLR was significantly associated with advanced TNM stage (adjusted OR, 3.26; p < 0.001), lymph node metastasis (LNM) (adjusted OR, 1.40; p = 0.021), and tumor local invasion (adjusted OR, 2.29; p < 0.001). NAT showed a modest negative correlation with dNLR (R = -0.138, p = 0.005). Mediation analysis indicated that dNLR partially mediated the relationship between NAT and tumor aggressiveness. Conclusions Reduced NAT is associated with increased tumor aggressiveness in HPSCC and LSCC, and this relationship may be partially mediated by elevated dNLR. The association appeared more pronounced in male patients. These findings suggest that local adiposity and inflammation may play a role in tumor behavior and warrant further investigation in future studies.